2015
DOI: 10.1002/bjs.9872
|View full text |Cite
|
Sign up to set email alerts
|

Portal vein embolization and its effect on tumour progression for colorectal cancer liver metastases

Abstract: Background: The aim of this study was to evaluate the long-term outcomes of patients with colorectal cancer liver metastasis (CRCLM) exhibiting disease progression after portal vein embolization (PVE). and 46⋅2 versus 52⋅2 months for those with resectable disease (P = 0⋅953). However, disease-free survival for patients with tumour progression after PVE was shorter than that for patients with stable disease (6⋅0 versus 20⋅2 months; P = 0⋅045). Response to neoadjuvant chemotherapy was the only significant factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 39 publications
0
29
0
1
Order By: Relevance
“…Moreover, a study by Simoneau et al showed no difference regarding OS even upon tumor progression after PVE. However, patients with tumor progression had significantly shorter DFS [23]. Recently, a systematic review and meta-analysis by Giglio and coworkers concluded that PVE has no negative impact on hepatic recurrence and OS [32].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a study by Simoneau et al showed no difference regarding OS even upon tumor progression after PVE. However, patients with tumor progression had significantly shorter DFS [23]. Recently, a systematic review and meta-analysis by Giglio and coworkers concluded that PVE has no negative impact on hepatic recurrence and OS [32].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, after PVE/PVL alone or in combination in the setting of TSH – with the latter having an even better chance to detect and remove small tumor deposits and metastases during step 1 – up to 24–41% of patients do not undergo stage 2 hepatectomy, mainly due to disease progression [12, 13, 16]. In an analysis by Narita of 80 intended and 61 performed TSH (dropout rate 24%), more than 2 CRLM detected in the FLR during step one were a negative predictor of not achieving the second step [16].…”
mentioning
confidence: 99%
“…One of the concerns about preoperative PVE is that stimulation of liver hypertrophy can also accelerate tumor growth in the embolized and non‐embolized liver lobe . Portal flow reduction in the embolized liver leads to an increase of arterial blood flow and, subsequently, growth of tumors including micrometastases could be induced, because liver tumors are mostly supplied by arterial blood.…”
Section: Specific Techniques To Increase Resectabilitymentioning
confidence: 99%
“…The details are described in the next section. From the viewpoint that liver hypertrophy after PVL/PVE may accelerate tumor growth, the left‐first approach has now become a mainstream strategy of TSH.…”
Section: Specific Techniques To Increase Resectabilitymentioning
confidence: 99%